Lactic acid of PLGA coating promotes angiogenesis on the interface between porous titanium and diabetic bone. Issue 15 (28th March 2018) - Hu, Xiao-Fan; Feng, Ya-Fei; Xiang, Geng; Lei, Wei; Wang, Lin
Abstract : PLGA-coating on 3D-printed porous titanium implants promoted the angiogenesis and osteointegration at bone-implant interface in diabetes by releasing lactic acid. Abstract : The diabetes-related high failure risk for endosseous implants needs efficacious methods to improve osteointegration on the bone-implant interface (BII). Poly(lactic- co -glycolic) acid (PLGA) is widely used in tissue engineering but its effects on the BII in diabetes remain unclear. To clarify this issue, 3D-printed porous titanium implants (TI) with and without PLGA coating were fixed in the bone defects of sheep in vivo, and vascular endothelial cells (VEC) and osteoblasts were incubated on the implant surface under normal conditions (NC) and diabetic conditions (DC) in vitro . The results showed that the PLGA coating promoted angiogenesis on the BII and the osteointegration of TI in diabetic sheep. The PLGA coating attenuated the DC-induced dysfunctions of VEC but not of osteoblasts. When VEC and osteoblasts were co-cultured in DC, the PLGA coating showed protective effects on the osteoblasts. Lactic acid (LA) but not glycolic acid (GA), both of which are degradation products of PLGA, induced similar effects to those of PLGA. These results suggest that PLGA coating on TI could promote angiogenesis in diabetes by its degradation production of LA, thus indirectly improving the bone formation on BII. Furthermore, PLGA exerted its effects, at least partially, through inhibiting the pathological effects of advanced glycation end products (AGEs) on the BII. This is the first study of the effects of PLGA on angiogenesis on the BII and the first findings on the inhibitory effects of PLGA on AGEs. Our findings demonstrate that PLGA is a promising interface-modification component for fabricating implants with better angiogenesis and osteointegration on the BII under diabetic conditions. This strategy might be applicable for reducing implant failure in diabetic patients.